Computer Based Accounting System to Improve Village Fund Financial Accountability - Malahayati, Rina; Hasan, Muridha; Pertiwi, Tri (International Journal of Economics (IJEC), 2025)
This study examines the implementation of a computer-based accounting system to enhance the accountability of village fund management in Pasir Bangun Village, Southeast Aceh. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and document analysis from August to December 2024. The results indicate that the system significantly improved financial document completeness from 58% to 92% and reduced reporting time from 47 days to 9 days. Key findings identify three critical success factors: (1) strong village leadership, (2) tiered mentoring by district government, and (3) cultural adaptation of the system through Acehnese language interface and integration with traditional village deliberation. Major challenges include limited electricity and internet infrastructure, human resource competency gaps, and resistance from older-generation village officials. The study recommends regular training funding allocations, village technology task forces, and basic infrastructure provisions as strategic measures. These findings contribute to the literature on village government digitalization by proposing an implementation model that integrates technical, social, and cultural aspects.